Shoulder Arthroplasty Outcomes After Prior Non-Arthroplasty Shoulder Surgery. Issue 3 (25th September 2018) - Frank, Rachel M.; Lee, Simon; Sumner, Shelby; Griffin, Justin; Leroux, Timothy; Verma, Nikhil N.; Cole, Brian J.; Nicholson, Gregory P.; Romeo, Anthony A.
Abstract : Background: The purpose of this retrospective study was to compare outcomes and complications in patients with and patients without a history of non-arthroplasty surgery on the ipsilateral shoulder who later underwent total shoulder arthroplasty (TSA) or reverse total shoulder arthroplasty (RTSA). We hypothesized that patients who had undergone prior surgery would have more complications and worse clinical outcomes. Methods: Consecutive patients who had undergone shoulder arthroplasty and had been followed for a minimum of 2 years were evaluated with the American Shoulder and Elbow Society scoring system (ASES), Simple Shoulder Test (SST), and Visual Analog Scale (VAS) assessments and with physical examination, including range-of motion assessments. Complications and outcomes in patients who had undergone prior surgery on the ipsilateral shoulder (PS group) were compared with those in patients without such a history (NPS group). Results: Data on 506 shoulder arthroplasties (263 TSA and 243 RTSA) were available for analysis. A total of 144 patients (28%) had an average of 1.9 ± 1.0 surgical procedures on the ipsilateral shoulder before arthroplasty. The average age in the PS group was significantly younger at the time of arthroplasty compared with the NPS group (61.6 ± 10.2 years compared with 68.2 ± 8.6 years, p = 0.035). At an average follow-up of 42.8 ± 16.4 months, both groups had significant improvements in ASES, SST, VAS, and range-of-motion values (p < 0.05 for all). All outcome scores in the PS group were significantly lower than those in the NPS group (p < 0.001 for all). The PS group also had a significantly higher complication rate than the NPS group (19.4% compared with 4.4%, p < 0.001), and multivariate regression analysis revealed that prior surgery was a significant independent predictor of postoperative complications. There were no differences between the PS and NPS groups in the number of postoperative infections (p = 0.679), reoperations (p = 0.553), or transfusions (p = 0.220). Conclusions: Patients who have a history of prior surgery on the ipsilateral shoulder derive benefit from shoulder arthroplasty, but their magnitude of improvement and final scores are lower than those of patients who do not have such a history. This information can be used to counsel this challenging patient population on expected outcomes following shoulder arthroplasty. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.